Color‐tunable and bright nonconjugated fluorescent polymer dots and fast photodegradation of dyes under visible light. Issue 2 (8th December 2021) - Han, Bingyan; Yan, Qifang; Xin, Ze; Liu, Qingdong; Li, Dan; Wang, Jiao; He, Gaohong
Abstract: Nonconjugated polymer dots (PDs) without largely conjugated structures entitle their advantages such as environment friendliness, nontoxicity, and intrinsic fluorescence. However, color‐tunable PDs remain a challenge. Herein, polyvinyl pyrrolidone (PVP) and ascorbic acid (AA) are used to synthesize nonconjugated PDs, namely, PA PDs with intensive blue emission. The introduction of a third component, m‐phenylenediamine (MPD), redshifted the emission to green. The as‐prepared color‐tunable blue to green emissive PDs exhibit excellent properties, whether in solution or in solid state, originated from the mechanism of clustering‐triggered emission (CTE) induced by the overlap of electron‐rich atoms, the strong inter/intrachain interaction. The quantum yields of blue and green PDs reached up to 15.07% and 28.22%, respectively. Furthermore, PA PDs were successfully applied to the highly efficient photocatalytic degradation for dyes: methylene blue (MB) and methyl orange (MO) were degraded by 89.9% and 93.8% within 20 min under visible light, respectively. Abstract : Color‐tunable and bright nonconjugated fluorescent polymer dots were achieved from blue to green emission, and blue emissive nonconjugated polymer dots showed fast photodegradation of dyes under visible light: methylene blue (MB) and methyl orange (MO) were degraded by 89.9% and 93.8% within 20 min, respectively.